The effect of training volume and growth on gymnastic performance in young women - Richards, J. E.; Ackland, T. R.; Elliott, B. C. (Pediatric Exercise Science, 1999)
Thirty-seven females, aged initially between 10 and 13.5 years, completed a mixed longitudinal study over 3.3 years to investigate the effect of training volume and growth upon gymnastic performance. Gymnasts undergoing high volume training (mean = 30 hrs/week: Group 1) and moderate volume training (mean = 15 hrs/week: Group 2) were tested at 4-month intervals on growth measures including height, mass, skinfolds, and segment lengths, as well as the strength of lower limb, upper limb, and trunk musculature. Functional gymnastic development was observed through the assessment of generic, whole body rotation tasks, a vertical jump, and a v-sit action. The high training volume gymnasts were significantly smaller but markedly stronger than those gymnasts in Group 2 despite the size disadvantage. Consequently, Group 1 gymnasts were able to produce higher velocities for front and backward rotations and a faster v-sit action. These training group differences remained significant after initial size differences were taken into account via an analysis of covariance.